The ephemeris of San Fernando - Salaverry García, Oswaldo (2001)
The first week of October is traditionally recognized as the week of the Peruvian Medicine, with the main event, the October 5, commemorating the death of Carrion, the student symbol of our Medical School. Probably involved in the halo, few remember to celebrate the anniversary of the Faculty, which forced or carelessly considered to match the same dates. A brief summary of our institutional history enable us to identify different ephemeris that should be remembered by our Alma Mater, naturally without compromising the iconic nature of death of Carrion.